Primary study on the probiotic properties of Lactobacillus casei LC 304.08 following international standard - Hong, Nguyen Ngoc; Giang, Van Huong; Phuong, Nguyen Thi; Ha, Dao Ngoc; Ha, Nguyen Duy; Hoang, Le Huy; Uyen, Nguyen Quynh; Vinh, Hoang Van (Vietnam Journal of Science and Technology, 2022)
Abstract Products containing beneficial bacteria for humans have been widely used recently. The bacteria in these products generally belong to the genus Lactobacillus. Among the species of this genus, Lactobacillus casei attracts a lot of interest due to their valuable properties. With these properties, many L.casei strains can be used as probiotics. Based on the recommendation of FAO/WHO for probiotic bacteria, in our study strain LC 304.08 was identified based on morphology and biochemical properties as well as nucleotide sequence of 16S rDNA. The strain was then evaluated for its properties in vitro such as the ability to survive at low pH and in the presence of bile salt, the ability to produce antibacterial substances and enzyme as well as its safety regarding hemolytic and antibiotic resistance. The results showed that the strain was identified as Lactobacillus casei. It survived well at low pH and in the presence of bile salt, and it produced β-galactosidase with the activity of 81 ± 1.1 (U/mL). In addition, the strain was safe regarding its hemolytic activity and antibiotic resistance.